The long shadow of bullying: Career consequences for an American cohort - Fraser Summerfield (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2024)
We document the long-run labor market consequences of youth bully victimization using NLSY97 data. Career outcomes measured at ages 19-40 account for life cycle bias. Victims exhibit lower earnings, lower job satisfaction and hold less-complex occupations. Fewer hours worked and shorter job tenure contribute to cumulative experience gaps that widen with age. Female respondents and adolescent victims are most significantly affected. A decomposition exercise shows that concurrent life-cycle health and education penalties explain half of the observed career penalties. Using household fixed-effects models and rich early-life covariates we show that selection into bullying on these dimensions cannot explain earnings penalties. Our results suggest a role for programs and policies that reduce health and human capital disparities of those bullied during youth.
Keywords: 330; Bullying; Life-cycle outcomes; Earnings; Non-cognitive skills; Human Capital